KAJI EKSPERIMEN OPTIMASI KOEFISIEN DAYA SKEA JENIS POROS DATAR DENGAN SUDU GABUNGAN SILINDER BERPUTAR DAN ROTOR SAVONIUS - Maria F Soetanto; Aryadi Suwono; Prihadi S Darmanto; Ari D Pasek (Mesin, 2004)
Horizontal Axis Wind Energy Conversion System (HAWECS) is more efficient than other Wind Energy Conversion Systems at the same condition [2,3]. Rotating cylindrical blade is taken as the substitute alternative to the airfoil blade considering that presence of lift force and its simple manufacturing production. The lift force generated by the rotating cylinder is known as the Magnus Effect [1,7,9]. The savonius rotor in this research is employed to propel the cylinder. This research conducted an experiment to optimize the energy conversion of a HAWECS which its blades consist of the combination of cylinder and savonius rotor. Two kind of blades were used in this experiment, i.e.blade with L/D (ratio of the length and diameter of cylinder) equals to 3 and 4. Three variations of wind velocities were used, i.e. 8.5 m/s, 9.7 m/s, and 10.2 m/s. Experimental results present that the blade with L/D ratio = 4 give more efficient than the L/D = 3, and the increase of power was reached if the wind velocity increases.